Ballistic behaviour of explosively shattered alumina and silicon carbide targets - Nanda, H.; Appleby-Thomas, Gareth J.; Wood, David C.; Hazell, Paul J. (Maney Publishing, 2011)
The resistance offered by three ceramic materials of varying strength that have been subjected to explosive loading has been investigated by depth-of-penetration testing. Each material was completely penetrated by a tungsten carbide cored projectile and the residual penetration into a ductile aluminium alloy backing material was measured. The resulting ballistic performance of each damaged ceramic was found to be similar implying that the resistance offered to the projectile by the damaged ceramic is not dependent on the intrinsic strength properties of the intact material. This was taken as evidence that the important controlling parameter for enhancing the ballistic performance of a damaged ceramic material was not the strength of the ceramic but rather the fragment morphology.
Keywords: ballistic impact; ceramic armour; comminuted material; strength of comminuted material; explosive shattering